2018
DOI: 10.3390/s18020355
|View full text |Cite
|
Sign up to set email alerts
|

The Response of HeLa Cells to Fluorescent NanoDiamond Uptake

Abstract: Fluorescent nanodiamonds are promising probes for nanoscale magnetic resonance measurements. Their physical properties predict them to have particularly useful applications in intracellular analysis. Before using them in intracellular experiments however, it should be clear whether diamond particles influence cell biology. While cytotoxicity has already been ruled out in previous studies, we consider the non-fatal influence of fluorescent nanodiamonds on the formation of reactive oxygen species (an important s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 55 publications
2
38
2
Order By: Relevance
“…Next to proliferation, one can also test the metabolic activity (e.g., by an MTT assay) or the membrane integrity (e.g., by a LIVE/DEAD assay) as measures for cell viability. These viability effects have been tested in response to nanodiamonds; FNDs were shown to have only minor effects on the proliferation capacity of yeast cells [13], and likewise only minor changes in functional effects were observed for several mammalian cell types [14,[26][27][28], demonstrating the excellent biocompatibility of FNDs. When focusing more on detail on oxidative stress, there are different strategies to explore this.…”
Section: The Many Faces Of Cell Viability and The Challenges In Measumentioning
confidence: 99%
See 1 more Smart Citation
“…Next to proliferation, one can also test the metabolic activity (e.g., by an MTT assay) or the membrane integrity (e.g., by a LIVE/DEAD assay) as measures for cell viability. These viability effects have been tested in response to nanodiamonds; FNDs were shown to have only minor effects on the proliferation capacity of yeast cells [13], and likewise only minor changes in functional effects were observed for several mammalian cell types [14,[26][27][28], demonstrating the excellent biocompatibility of FNDs. When focusing more on detail on oxidative stress, there are different strategies to explore this.…”
Section: The Many Faces Of Cell Viability and The Challenges In Measumentioning
confidence: 99%
“…However, there are other ways of assessing the cell viability and evaluating the response of cells. Prior to further investigation of the actual role of ROS in aging mechanisms, the oxidative response of yeast cells to FND internalization should be examined with state of the art methods, as was done previously for mammalian cells [14]. This is crucial to discriminate a possible FND-related effect from an age-related effect, which will be the subject of future studies.…”
Section: Introductionmentioning
confidence: 99%
“…For biological applications, the excellent biocompatibility of fluorescent nanodiamonds is also crucial [9]. In several previous studies, FNDs are introduced in mammalian cells and have shown no negative effects [10][11][12]. From these studies, it is known that mammalian cells passively take up FNDs in different ways depending on the cell type and exact conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Hemelaar et al investigated viability, but also nonfatal responses of HeLa cells to the presence of nanodiamonds . In their comprehensive study, they investigated reactive oxygen species production, as well as the regulation of stress‐related genes and their translation to proteins.…”
Section: In Vitro Biocompatibilitymentioning
confidence: 99%